EFEKTIVITAS PEMBERDAYAAN MASYARAKAT OLEH KELOMPOK SADAR WISATA (POKDARWIS) DALAM MENGEMBANGKAN PARIWISATA BERKELANJUTAN (Studi pada Pokdarwis Minang Rua Bahari di Desa Kelawi, Kecamatan Bakauheni, Kabupaten Lampung Selatan) - Yatmaja, Panji Try (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2019)
Sustainable tourism is promoting empowerment which makes the community as the main actor in the business tourism as well as enjoys the larger benefits of tourism by minimizing the negative impact of the development of tourism. The development of tourism in the Kelawi village, sub-district Bakauheni, South Lampung Regency is done with the establishment of Pokdarwis Minang Rua Bahari in an effort to enhance the role of the community in the tourism industry. This research aims to analyze the community empowerment and measuring the effectiveness of pokdarwis empowering communities in developing sustainable tourism. A descriptive type of research with a qualitative approach. The results showed community empowerment phases has not been conducted optimally if viewed from the community involvement in the development of tourism. However, in the organizational aspect, Pokdarwis Minang Rua Bahari been able to shape the initiative and creating innovation in the management of tourism. The level of community empowerment shows the economic and political aspects have been well established, whereas the psychological and social aspects of it are still a constraint. The effectiveness of pokdarwis empowering communities in sustainable tourism development is quite good, but there are still constraints in increasing community involvement in the development of tourism. Department of Tourism and Culture of South Lampung Regency should perform empowerment through coaching and training in accordance with the potential of natural resources or cultural belonging to the village of Kelawi, the Kelawi Village Government can make use of the website and for the promotion of village tourism service, Pokdarwis Minang Rua Bahari must dare to establish cooperation with various parties, and the villagers of Kelawi should create an environment that reflects as a tourist village. Key Words: Effectiveness, Community Empowerment, Pokdarwis (Tourism Awareness Group), Sustainable Tourism.